Electrospun Nanofibers for Biomedical Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Electrospinning is a versatile and effective technique widely used to manufacture nanofibrous structures from a diversity of materials (synthetic, natural or inorganic). The electrospun nanofibrous meshes’ composition, morphology, porosity, and surface functionality support the development of advanced solutions for many biomedical applications. The Special Issue on “Electrospun Nanofibers for Biomedical Applications” assembles a set of original and highly-innovative contributions showcasing advanced devices and therapies based on or involving electrospun meshes. It comprises 13 original research papers covering topics that span from biomaterial scaffolds’ structure and functionalization, nanocomposites, antibacterial nanofibrous systems, wound dressings, monitoring devices, electrical stimulation, bone tissue engineering to first-in-human clinical trials. This publication also includes four review papers focused on drug delivery and tissue engineering applications.